(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
Product to the affectations happened in the distribution circuits by the faults happened in its the investigation arises: Application of the Loop Automation in a net of distribution of half tension, looking for design a system of protection that is able to isolate the fault in the smallest tract in the possible circuit, avoiding a high number of clients so is affected. In the work is carried out a brief description of the protection commonly used in the distribution systems demonstrating as these they are not able to limit the fault to the smallest possible area, and of how that is possible using the recloser of Nulec working under the Loop Automation. Also, is proposed a work methodology that facilitates the design of this system of protection getting in the analyzed circuits the faults affect to the smallest number of clients.